Teacher´s perception of academic supervision of the school headmaster - AHMAD, A.; SAEFURROHMAN, S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The aim of this study is to know about the teacher´s perception of academic supervision activities, which is taken by the school headmaster. 116 teachers from the elementary school up to the senior high school in the Banyumas district become the subject of this study. The result of this study shows that more than 50% of the respondent thought that the headmaster had done a well-planned supervision activity, which is consisted of the schedule arrangement, program, and supervision instrument. More than 50% of respondents thought that headmaster as a supervisor makes teachers have high performance as a model teacher.RESUMEN El objetivo de este estudio es conocer la percepción de los maestros sobre las actividades de supervisión académica que toma el director de la escuela. 116 docentes desde la escuela primaria hasta la escuela secundaria superior en el distrito de Banyumas se convierten en el tema de este estudio. El resultado de este estudio muestra que más del 50% de los encuestados pensaba que el director había realizado una actividad de supervisión bien planificada que consistía en la disposición del programa y el instrumento de supervisión. Más del 50% de los encuestados pensó que el director como supervisor hace que los maestros tengan un alto rendimiento como maestros modelo.